Consumer perceptions towards sales promotion tools applied by hypermarket in Kuching - Chai,, Fang Fang. (UNIMAS, 2009)
Sales promotion has been constantly growing since the 1960’s and today, it is one of the key factors in the promotional mix. Since the hypermarket format is very new in Kuching retail industry, the choice of appropriate sales promotion tools is important decisions for the retailers. The purpose of this study is to provide a general understanding on consumer hypermarket shopping behaviour in Kuching. This study identifies the consumer segments that visit the hypermarket in Kuching, the sales promotion tool that is favoured most when applied in the hypermarket format, and the effects of seven sales promotion tools, namely sample, coupon, cash refund offer, price-off, premium, patronage reward, and contest and sweepstake on consumers’ purchase intentions. The data base comprising a total of 285 hypermarket consumers in Kuching, Sarawak were surveyed using structured questionnaire. The results show that price-off is the most favoured sales promotion tool but it does not have any effect on consumes’ purchase intentions.Cash refund offer, coupon, premium, and contest and sweepstake are associated with consumers’ purchase intentions. Details of the findings and the implications are discussed.